1995
DOI: 10.1007/bf00193173
|View full text |Cite
|
Sign up to set email alerts
|

A histological study on experimental autoimmune myocarditis with special reference to initiation of the disease and cardiac dendritic cells

Abstract: The precise mechanism of myosin-induced autoimmune myocarditis is unknown. The purpose of the present study was to define the immunohistological and ultrastructural characteristics of the infiltrating cells, especially in the initial phase of the myocarditis. It was demonstrated that OX6-positive dendritic cells first infiltrated the cardiocytes on day 13 after immunization. After day 17, OX6-positive cells, which possessed elongated irregular-shaped processes on the cell surface but contained few phago-lysoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
(19 reference statements)
3
7
0
Order By: Relevance
“…In areas of inflammation, cells bearing both ED1 and ED3 were seen. Our observations of the distribution of cells positive for these two antigens in autoimmune myocarditis agrees with that reported by Suzki [39] and mirrors descriptions of inflammation in other tissues, both autoimmune and injury induced [40,41]. The prevailing opinion is that these macrophage specific monoclonal antibodies ED1, ED2 and ED3 mark unique subsets of cells belonging to the monocyte/macrophage lineage.…”
Section: Discussionsupporting
confidence: 93%
“…In areas of inflammation, cells bearing both ED1 and ED3 were seen. Our observations of the distribution of cells positive for these two antigens in autoimmune myocarditis agrees with that reported by Suzki [39] and mirrors descriptions of inflammation in other tissues, both autoimmune and injury induced [40,41]. The prevailing opinion is that these macrophage specific monoclonal antibodies ED1, ED2 and ED3 mark unique subsets of cells belonging to the monocyte/macrophage lineage.…”
Section: Discussionsupporting
confidence: 93%
“…MIP-1␣, therefore, may be produced primarily by OX6-positive or ED2-positive cells before the onset of EAM. OX6 ϩ MIP-1␣ ϩ cells were seen approximately one half as frequently as ED2 ϩ MIP-1␣ ϩ cells in normal rats, as reported previously (Suzuki, 1995). Before the onset of EAM, the number of OX6 ϩ…”
Section: Toyozaki Et Alsupporting
confidence: 85%
“…OX6 mouse anti-rat Ia (MHC class II) antibody has been used to identify cardiac dendritic cells (DC) (Darden et al, 1987). Immunohistochemical and ultrastructural findings have suggested that OX6-positive cells present in the early phase of EAM were cardiac DC (Suzuki, 1995). In general, DC can activate immunologically naive T cells in the initiation of cell-mediated immune reaction (Steinman, 1991).…”
Section: Mip-1␣mentioning
confidence: 99%
“…13 The primary antibodies (Serotec) used were as follows: OX62 antibody to recognize an integrin or integrin-like molecule present on DCs and ␥␦ T cells, 16 V65 antibody to specifically detect ␥␦ T cells, 17 OX6 antibody to recognize major histocompatibility complex (MHC) class II-expressing cells, including DCs, monocytes, and B lymphocytes, 13 ED1 antibody to detect inflammatory macrophages, 13 ED2 antibody to detect tissue macrophages, 13 W3/25 antibody to detect helper T lymphocytes and macrophages, 13 and OX8 antibody to detect cytotoxic/suppressor T lymphocytes. 13 W3/25 antibody is regarded as being directed against the rat homologue of CD4.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…12 Accordingly, DCs appear to play an important role during the initial antigen-priming process of myocarditis. 11,13 Therefore, to clarify the FcR-mediated effects, we investigated the effects of immunoglobulin on autoimmune giant cell myocarditis with the analyses of immunologic behaviors of DCs and myocardial cytokines.…”
mentioning
confidence: 99%